The Role of The Leadership of Ma’had Al-Buus Al-Islamiah in The Development of The Islamic Generation in Yala, Southern Thailand - Muhammadnur Kora; Ahmad Salim; Kana Safrina Rouzi; Ahmad Syamsul Arifin; Aida Hayani (TADRIS: Jurnal Pendidikan Islam, 2024)
The function of educational institutions has occasionally been crucial, particularly in the development of the younger generation to be more qualified. Through the educational institutions of the practitioners, the younger generation is formed, among other things. The purpose of this study is to find out how the role of the leader of Ma’had Al-Buuss Al-Islamiah in Islamic Generation Building in Raman Yala, and what is the leadership's biggest challenge? This research is a qualitative study that is used to analyse phenomena, beliefs, and the way that both individuals and groups of people think. Primary data types, which can be examined and acquired on-site, are used in research. Ways for gathering data, including documentation, interviews, and observation. Data analysis through data reduction, data display, and inference. Data approval using source triangulation techniques. This investigation found that the role of Master Haji Muhammad Ramli Kora was very influential in the education institutions and the public in particular in the district of Raman Province of Yala.